PERHITUNGAN UNIT COST PADA PASIEN COVID 19 DI INSTALASI RAWAT INAP DI RS. ROEMANI MUHAMMADIYAH SEMARANG - Agustyarum Pradiska Budi; Umi Nafisah (Universitas Duta Bangsa Surakarta, 2023)
The state bears the expense of caring for Covid 19 patients through BPJS, therefore delays in claim payments have an impact on the hospital's financial status. In order to swiftly change expenses, hospitals must determine the Covid 19 patient unit cost. This study aims to determine the unit cost of treating Covid 19 inpatients with comorbid and non comorbid using the Activity Based Costing (ABC) method in Roemani Muhammadiyah Semarang hospitals. This descriptive research method with a quantitative approach uses documentation study data collection techniques in medical record documents for inpatient installations for Covid 19 patients and unstructured interviews. Quantitative analysis of unit cost calculation using Activity Based Costing (ABC) method. According to the study's findings, Covid 19 patients cost Rp 3,236,126.00 per unit in indirect expenditures. Unit expenses for Covid 19 patients without co-morbid conditions total Rp. 21,471,091.00, while co-morbid patients' unit costs total Rp. 31,172,433.00. Based on the results using the ABC method compared to hospital rates and the rates paid by BPJS, the hospital does not experience a loss. Recommendations given to hospitals by periodically adjusting hospital rates and for the government can be used as input for the economic model in paying BPJS claims in the future.